Parkinson's disease and the welding job: are both related? - Mochtar, Iqbal; Mansyur, Muchtaruddin (Faculty of Medicine, Trisakti University, 2020)
Up to the present, there has been a controversy on the relationship between Parkinsonâ€™s disease and the welding job. The aim of this study was to obtain evidence-based information regarding the relationship between Parkinsonâ€™s disease and the welding job through an evidence-based case report derived from a literature review. The review was conducted through a method of search and selection of articles in the Pubmed, Cochrane Library and JSTOR databases aimed at answering the study question. The process of searching articles used the keywords â€œWeldingâ€ OR â€œWelderâ€ AND â€œParkinsonâ€. Article selection was performed using the defined inclusion and exclusion criteria. At the initial search, 117 articles were retrieved from the three databases. Following the selection process, three articles remained, which consisted of one systematic review and two observational studies. Comparing the selected articles, the systematic review of Mortimer et al. is more relevant and appropriate for answering the clinical question. Mortimer et al. used a meta-analytical method, applied strict inclusion and exclusion criteria and excluded studies that potentially led to bias effects, lack of validity or inadequate statistical methods. Based on the selected evidence-based resources, Parkinsonâ€™s disease is not related to the welding job. The welding job, however, may produce clinical symptoms and signs resembling Parkinsonâ€™s disease, known as manganism.